Synthesis of poly (hydroxamic acid) ligand from polymer grafted khaya cellulose for transition metals extraction - Md Lutfor Rahman; Bablu Hira Mandal; Shaheen M. Sarkar; Nor Asiken Abdul Wahab; Mashitah Mohd Yusoff; Sazmal E. Arshad; Baba Musta (The Korean Fiber Society, 2016)
A cellulose-graft-poly(methyl acrylate) was synthesized by free radical initiating process and the ester functional groups were converted into the hydroxamic acid ligand. The intermediate and final products are characterized by FT-IR, FE-SEM, HR-TEM and XPS technique. The pH of the solution acts as a key factor in achieving optical color signals of metal complexation. The reflectance spectra of the [Cu-ligand]n+ complex was found to be a highest absorbance at 99.8 % at pH 6 and it was increased upon increasing of Cu2+ ion concentrations and a broad peak at 700 nm was observed which indicated the charge transfer (π-π transition) metals-Cu complex. The adsorption capacity of copper was found to be superior (336 mg g−1) rather than other transition metals such as Fe3+, Co3+, Cr3+, Ni2+, Mn2+ and Zn2+ were 310, 295, 288, 250, 248 and 225 mg g-1, respectively at pH 6. The experimental data of all metal ions fitted significantly with the pseudo-second-order rate equation. The transition metal ions sorption onto ligand were well fitted with the Langmuir isotherm model (R2>0.99), which suggested that the cellulose-based adsorbent known as poly(hydroxamic acid) ligand surface is homogenous and monolayer. The reusability of the poly(hydroxamic acid) ligand was checked by the sorption/desorption process up to ten cycles without any significant loss in its original sensing and removal performances.